Best project management practice to attain project success, based on the success criteria - Chaher, Zid Chaher; Soomro, Ali Raza; Salleh, Nurul Hamiruddin (2017)
The project management is described as managing resources on a given activity of an organization unit dedicated in order to meet the attainment of a goal and a successful completion of the development project. Many researchers have been endeavoring to develop the best practice of project management in conformance with predetermined performance specifications to avoid delays, overrun cost, quality reduction and to meet the specific requirements of stakeholders as well. This research paper reviews the literature on the project management relevant to the project success and determines the specific success criteria and the value of the iron triangle cost-time-quality to better practice for the project management. Moreover, this paper proposes that the project success can be defined in terms of the integration of the project management and success criteria “Cost-Time-Quality” to meet the satisfaction and the expectation of the stakeholders.